The Effect of Midfulness Meditation in Maintaining Blood Pressure in Elderly People with Hypertension: Systematic Review - Sinurat, Diana Nurhayati; Sahar, Junaiti; Rekawati, Etty; Rachmawati, Utami (GLOBAL HEALTH SCIENCE GROUP, 2024)
Elderly with hypertension is group necessary vulnerability​ handling in giving care nursing in a way comprehensive . The purpose of review from systematic This is explore about influence deep mindfulness meditation maintain pressure blood in the elderly with hypertension . Data obtained from Embase, Pubmed, Proquest and Ebscohost databases start from 2019-2023 . Collected articles in review systematic using the keywords